2017
DOI: 10.18203/2349-3933.ijam20175178
|View full text |Cite
|
Sign up to set email alerts
|

The total leucocyte count: its utility in dengue

Abstract: Background: Dengue infections are public health concerns in India, where they occur in epidemics and have a high mortality in the advanced stages. Clinical features are nonspecific, and diagnosis is supported by lab features. One of these lab tests include total leucocyte count-easily available, simple and cost effective which is useful in small rural set ups for early diagnosis and prognosis of dengue. The aim of this study is to analyse the total leucocyte count patterns in dengue and assess its utility as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…A patient with dengue had more severe thrombocytopenia on days 4-7, and the platelet count reached the lowest number on day 5 [26]. The pathogenesis of thrombocytopenia and leukopenia is suggested that dengue virus induced bone marrow suppression and depressed platelet and leukocyte synthesis and resulted in thrombocytopenia and leukopenia [7], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A patient with dengue had more severe thrombocytopenia on days 4-7, and the platelet count reached the lowest number on day 5 [26]. The pathogenesis of thrombocytopenia and leukopenia is suggested that dengue virus induced bone marrow suppression and depressed platelet and leukocyte synthesis and resulted in thrombocytopenia and leukopenia [7], [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dengue virus is a mosquito-transmitted virus that infects millions humans each year [5]. This virus is transmitted to humans through the bites of infected Aedes mosquitoes primarily by Aedes aegypti and Aedes albopictus mosquitoes [6], [7]. Infected human is the main carrier and spreader of DENV, the virus then is transmitted to uninfected mosquitoes for subsequent transmission.…”
Section: Introductionmentioning
confidence: 99%
“…26 Increased duration for the WBC to recover increase one's susceptibility to various infections. In the study by Joshi AA et al 27 , 47 cases of leucopenia (36%) out of 132 total cases were associated with thrombocytopenia. They reported that leucopenia is an early marker of dengue and association of leucopenia with thrombocytopenia suggests that it could be one of the prognosticators of severe dengue.…”
Section: Section: Medicinementioning
confidence: 94%
“…They reported that leucopenia is an early marker of dengue and association of leucopenia with thrombocytopenia suggests that it could be one of the prognosticators of severe dengue. 27 Verdeal JC et al 11 reported that leukopenia could be a marker of severe dengue. This points to the importance of evaluating WBC count also in the prognosis of dengue fever and should be explored in further research.…”
Section: Section: Medicinementioning
confidence: 99%
“…Gejala dan tanda IVD diikuti dengan perubahan parameter laboratorium hematologi seperti trombositopenia, leukopenia, dan hemokonsentrasi (Ghazali et al, 2013;Khandelwal & Khandelwal, 2017;Tsai et al, 2017). Perubahan parameter tersebut memburuk seiring dengan beratnya IVD (Joshi et al, 2017;Simmons et al, 2015). Meskipun pendapat ini ditentang oleh peneliti yang lain karena tidak adanya hubungan yang bermakna antara IVD dengan derajad trombositopenia dan peningkatan hematokrit (Wiwanitkit & Manusvanich, 2004).…”
Section: Pendahuluanunclassified